Childhood adversity and later life prosocial behavior: A qualitative comparative study of Irish older adult survivors - Rohner, Shauna L.; Salas Castillo, Aileen N.; Carr, Alan; Thoma, Myriam V. (Frontiers in Psychology, 2022)
Objective Although childhood adversity can have lasting effects into later life, positive adaptations have also been observed, including an increased tendency toward prosocial behavior. However, little is known about the link between childhood adversity and later life prosocial behavior, with a particular scarcity of research on intrafamilial childhood adversity. Therefore, this study aimed to examine older adult's experiences of childhood adversity and identify mechanisms linked to prosocial behavior. Two adversity contexts (intrafamilial and extrafamilial) were compared to explore individual, as well as broader cultural and contextual mechanisms linking childhood adversity and later life prosocial behavior. Method Semi-structured interviews (60–120 min) were conducted with N = 29 Irish (older) adult survivors of childhood adversity: n = 12 intrafamilial survivors (mean age: 58 years, range: 51–72), n = 17 institutional survivors (mean age: 61 years, range: 50–77). Interviews were analyzed using the framework analysis method, with reference to the conceptual model of altruism born of suffering. Results Five themes were identified on prosocial mechanisms, with three themes in both survivor groups (enhanced empathy, self-identity, amelioration), and two group-specific themes (compassion fatigue in intrafamilial survivors; denouncing detrimental social values in institutional survivors). Conclusion Results identified motivational processes and volitional factors linked to later life prosocial behavior. Connections to caring roles, (lack of) support, and social norms in childhood, as well as the need for a sense of purpose and meaning from the adversities in adulthood, highlight potential targets for psychotherapeutic intervention to promote prosocial responding and positive adaptation for childhood adversity survivors.